2023
DOI: 10.1136/tc-2023-057974
|View full text |Cite
|
Sign up to set email alerts
|

Dissuasive cigarettes as a tobacco control measure: a scoping review

Abdulmohsen Hamdan Al-Zalabani,
Sarah S Monshi,
Ahmed Fahd Al-Ahmadi
et al.

Abstract: ObjectiveThe aim was to identify and review the research literature on dissuasive cigarettes, including key concepts, types, sources of evidence and research gaps.Data sourcesPubMed, Scopus and Web of Science databases were searched up to January 2023 with no language or date restrictions. All study designs were included. Reference lists of the identified studies were manually searched. Studies on tobacco products other than cigarettes or on external cigarette packaging alone were excluded.Study selectionTwo r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…The review also identified a gap in the research, wherein all the studies were conducted in North America, Europe, Australia, and New Zealand. The current study tries to fill this gap by investigating the perceptions of the effectiveness of dissuading the use of cigarettes in a Middle Eastern population 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The review also identified a gap in the research, wherein all the studies were conducted in North America, Europe, Australia, and New Zealand. The current study tries to fill this gap by investigating the perceptions of the effectiveness of dissuading the use of cigarettes in a Middle Eastern population 28 .…”
Section: Discussionmentioning
confidence: 99%